Air Stacking: A Detailed Look Into Physiological Acute Effects on Cough Peak Flow and Chest Wall Volumes of Healthy Subjects - Sarmento, Antonio; de Andrade, Armèle F Dornelas; Lima, Íllia Nadinne Df; Aliverti, Andrea; de Freitas Fregonezi, Guilherme Augusto; Resqueti, Vanessa R (Respiratory care, 2017)
Air stacking (AS) is a lung insufflation method that requires the use of a manual insufflator to provide air volumes higher than inspiratory capacity. Neuromuscular patients benefit the most from the maneuver; however, the acute effects of AS in healthy subjects are still unclear. Twenty healthy subjects (8 males) were studied by optoelectronic plethysmography to investigate the immediate effects of AS on cough peak flow, operational volume variations, distribution of these volumes in the chest wall compartments (pulmonary rib cage, abdominal rib cage, and abdominal), breathing pattern, and shortening velocity of the respiratory muscles during a protocol that included vital capacity maneuvers and spontaneous coughs before and after AS. Statistically significant increases in cough peak flow ( < .03) and inspiratory capacity ( < .001) were found immediately after AS. During its application, the pulmonary rib cage compartment was the largest contributor ( = .002) to chest wall volume displacement. A significant increase in chest wall tidal volume ( < .001), mainly in the pulmonary rib cage ( < .001), was observed. Significant increases ( < .001) in end-inspiratory chest wall volume were observed with main distribution in pulmonary ( < .001) and abdominal rib cage ( = .01). Significant increases in shortening velocity index of inspiratory muscles ( < .001), expiratory muscles ( < .001), and diaphragm ( < .001) were also observed. In addition, significant decreases in expiratory time ( < .001) and increases in duty cycle ( = .02), breathing frequency ( = .02), minute ventilation ( < .001), maximum inspiratory ( < .001), and expiratory flow ( < .001) were observed. In healthy subjects, cough peak flow and chest wall volumes can be increased immediately after the application of the AS maneuver.